2022
DOI: 10.1177/20420986221125006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance: reporting requirements throughout a product’s lifecycle

Abstract: Comprehensive methods for evaluating safety are needed to objectively assess the full risk profile of a medication. The confidence of the prescribing provider in the safety and effectiveness of pharmaceuticals is extremely important. Pharmacovigilance is a key component of drug safety regulatory processes and is paramount for ensuring the safety profile of medications used to treat patients. All participants in the healthcare system, including healthcare providers and consumers, should understand and meaningfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Notably, our study revealed previously undetected hepatotoxic adverse events associated with CDK4/6is. While clinical trials have focused on laboratory-sensitive AEs, spontaneous reporting data have provided essential real-world insights, emphasizing the significance of vigilant pharmacovigilance for identifying rare adverse reactions ( FDA, 2009 ; Lucas et al, 2022 ). AE analysis of palbociclib revealed liver-related signals (ascites, liver disorders, increased liver function), consistent with increased risk in new and long-term users ( Beachler et al, 2021 ; Finn et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our study revealed previously undetected hepatotoxic adverse events associated with CDK4/6is. While clinical trials have focused on laboratory-sensitive AEs, spontaneous reporting data have provided essential real-world insights, emphasizing the significance of vigilant pharmacovigilance for identifying rare adverse reactions ( FDA, 2009 ; Lucas et al, 2022 ). AE analysis of palbociclib revealed liver-related signals (ascites, liver disorders, increased liver function), consistent with increased risk in new and long-term users ( Beachler et al, 2021 ; Finn et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacovigilance is scientific and data gathering activity relating to the detection, monitoring, understanding, and prevention of adverse events (AEs) for a medicine, which is a key component of drug safety regulatory processes and principally involves the identification and evaluation of safety signals associated with the use of a medicinal product ( Lucas et al, 2022 ). Medicine safety monitoring is a continuous and dynamic process throughout all the phases of the life cycle of a drug because although drug safety evaluation is very rigorous and thorough in a pre-clinical trial, these studies are conducted on limited numbers of patients that are selected based on strict eligibility criteria, meaning they do not fully represent real-world populations in limited duration, and it is difficult to detect rare and long-term adverse reactions (ADRs) ( Trifirò and Crisafulli, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…While safety assessments in clinical trials offer insights into AEs within the indicated population, these studies have limitations due to their duration and predefined patient criteria. Consequently, potential safety concerns may emerge in real-world settings that were not apparent during clinical trial evaluations [9]. No substantial evidence has been accumulated to address the uncertainty regarding the association of GLP-1RA with suicide or self-injury to date.…”
Section: Introductionmentioning
confidence: 99%